Status Gizi dengan Kejadian Anemia pada Remaja: Literatur Review - Setianingsih, Lilis Zuniawati (Jurnal Ilmiah Kesehatan Delima, 2023)
Objectives of this paper is to determine the relationship between nutritional status and the incidence of anemia in adolescents. The literature review study is a method used in collecting data or sources related to a particular topic that can be obtained from various sources such as journals, books, the internet, and other libraries. The article search stage uses the keyword "The relationship of nutritional status with the incidence of anemia in adolescents" with a total of 10 articles in vulnerable time ranging from the last 5-10 years. The result shows based on journals that have been analyzed from a total of 10 studies, there are 2 studies showing no relationship between nutritional status and the incidence of anemia in adolescent girls, and 8 research results stating that there is a relationship between nutritional status and the incidence of anemia in adolescent girls. This is caused by several factors, including adolescent girls experiencing anemia caused by irregular eating patterns, abstinence from eating eggs / meat / fish, not like to eat vegetables, eating habits of fast food, and junk food. Adolescent girls who have menstruated are at risk of iron deficiency anemia, due to the amount of blood lost during one menstrual period. Tujuan artikel ini untuk mengetahui hubungan status gizi dengan kejadian anemia pada remaja. Desain penelitian ini adalah literature review Studi literature review adalah cara yang digunakan dalam mengumpulkan data atau sumber yang berhubungan pada sebuah topik tertentu yang bisa didapat dari berbagai sumber seperti jurnal, buku, internet, dan pustaka lain. Tahap pencarian artikel menggunakan kata kunci “Hubungan status gizi dengan kejadian anemia pada remaja” dengan jumlah 10 artikel dalam rentan waktu mulai dari 5-10 tahun terakhir. Hasil Penelitian menunjukkan berdasarkan jurnal-jurnal yang telah dianalisis dari jumlah 10 penelitian terdapat 2 penelitian menunjukan tidak terdapat hubungan status gizi dengan kejadian anemia pada remaja putri, dan 8 hasil penelitian menyatakan terdapat hubungan status gizi dengan kejadian anemia pada remaja putri. Hal ini disebabkan oleh beberapa faktor, meliputi remaja putri mengalami anemia disebabkan karena pola makan yang tidak teratur, pantangan makan telor/daging/ikan, tidak suka mengonsumsi sayur, kebiasaan makan makanan fast food, dan junk food. Remaja putri yang sudah mengalami menstruasi beresiko terjadi anemia defisiensi zat besi, karena jumlah darah yang hilang selama satu periode haid.